2015
DOI: 10.1111/jcmm.12451
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of matrix remodelling phenotype in gingival fibroblasts by substratum topography

Abstract: Gingival connective tissue often has a composition resembling that of scar surrounding dental implant abutments. Increased cell adhesion, α-smooth muscle actin (α-SMA) expression and increased extracellular matrix deposition are a hallmark of fibrotic cells, but how topographic features influence gingival fibroblast adhesion and adoption of the α-SMA positive myofibroblast phenotype associated with scarring is unknown. The purpose of the present study was to demonstrate whether implant topographies that limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 55 publications
2
24
0
1
Order By: Relevance
“…Previous research has shown that the modification of the substrate modulates FA sites [ 11 , 62 ]. For example, FAs have been reported to increase on smoother surfaces compared to rougher surfaces [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the modification of the substrate modulates FA sites [ 11 , 62 ]. For example, FAs have been reported to increase on smoother surfaces compared to rougher surfaces [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Anselme et al have indicated potential positive effects for grooves in metals (Anselme et al, 2004). We further note that other cell types have been shown to be responsive to topographies in metals -again though, roughened rather than grooved (Lee et al, 2014;Kim et al, 2015).…”
Section: Perspectives On Cell-materials Interactionsmentioning
confidence: 66%
“…Fabrication of each topography was performed as previously described [ 16 , 21 ]. Briefly, Commercially-pure titanium (Cp-Ti) (Baoji Titanium Industry Co., Ltd., Baoji, China) was cut into 1-mm thick discs from Cp-Ti rods 15 mm in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that sand blast, large grit, acid-etch (SLA) roughened titanium topographies can be utilized to reduce myofibroblast differentiation in HGFs. The roughened topographical features induce nascent adhesion formation in HGFs which attenuates α-SMA expression, fibronectin synthesis, stress fiber assembly, and is concomitant with an upregulation of genes associated with matrix remodeling [ 21 ]. This study provides direct evidence that alterations in titanium substratum roughness can be utilized to reduce myofibroblast differentiation of HGFs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation